Peningkatan Motivasi Belajar Matematika Siswa Melalui Pembelajaran Matematika Realistik Indonesia - Rino Richardo; Ahmad Anis Abdullah; Muhammad Najib Mubarok; Dyahsih Alin Sholihah; Ardiyaningrum, Martalia; Esti Nawangsasi; Sri Wulandari Danoebroto; Abdul Tarom; Sulastri Sulastri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Mathematics is an important subject for students to master in facing the challenges of the 21st century. However, there are still many students who experience difficulties in learning mathematics. This is because learning mathematics is abstract and far from life. Therefore, the student mathematics education study program community service team introduced the Indonesian realistic mathematics education (PMRI) learning model at MTs Janki Dausat to increase student motivation in learning mathematics. As a result of this activity, students become motivated and enjoy learning mathematics, which can be seen from the students' enthusiasm and activeness in learning mathematics.